KONSTRUK SOSIAL DALAM KONVERGENSI HISAB DAN RUKYAT - Sakirman, Sakirman (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2017)
Hisab and rukyat issues have confiscated the energies of Muslims so great, it makes ukhuwah sometimes disturbed even in the celebration of Eid and Eid al-Adha. For a long time we are transfixed and chained to the problem only but not on the solution. As if the problem is merely the difference of the method of reckoning (astronomical calculations) and rukyat (hilal observations) that are impossible to unite, it is equally impossible to unite different schools of thought. The debates of the strongest arguments between the proponents of hisab and rukyat have been going on for hundreds of years, but the result has deepened the gap. This paper is trying to discuss the two problems mentioned above, to focus more on the discussion, the issues to be discussed are the concept of hisab and rukyat, history of hisab and rukyat, the strength and weaknesses between hisab and rukyat, the matched concept of hisab rukyat in Indonesia.